Local journalists and the digital challenge - Correia, João Carlos (2021)
The newsmaking process is increasingly occurring through online platforms. That is a challenge for both the media and journalists, who try to make this transition by seeking new ways of interacting with people who they used to look as quiet and far-to-reach audiences. Such is the specific case of local media journalists who work and live-in territories with populations linked by strong ties of closeness and neighborhood. That becomes particularly relevant in Portugal because the country has most of the population concentrated around the major cities along the coast at the expense of peripherical towns from the hinterland. A democratic sense of community of small and medium-sized cities in the Portugal hinterland implies symbolic production mechanisms that strength in e sense of belonging to those communities. The present study aims to identify the tools and content used and produced by the local media of the central region of Portugal, to understand the role played by digital technologies in this transition to the needs of the new digital ecosystem. To understand the phenomena, a survey was carried away next to a sample of journalists (n=107) from 41 newsrooms belonging to local media outlets from the Centre of Portugal the region with the more significant presence of local and regional media in the country. Even though social media and mobile phones are becoming part of the daily life of local journalists, empirical research often shows that real interactivity with the community seems to be exercised by only a few. This contradicts the defended idea that the long-term viability of a regional press implies using practices and routines for gathering information and reporting that reflect citizen engagement and public participation.